Movie in guidance and counseling service: could it help students to improve their problem-solving skill? - Yuni Irawati, Ratih Indah; Bariyyah, Khairul; Soejantoe, Laily Tiarani; Pambudi, Parid Rilo (Konselor, 2020)
This study uses films to provide positive stimulation for students. So that students can develop self-confidence and independence in solving problems. The problems that relate to personal, social, academic, and career. The purpose of this study is analyze the used of films in group guidance service to improve students' problem solving skills. This used experimental study with one group pretest-posttest design. The participants were ten junior high school students with low level of problem-solving skill. They were selected using purposive sampling technique. Problem-solving skill scale was employed as the instrument of the study. The reliability test shows the reliability coefficient of 0.926. The data were analyzed using Wilcoxon Sign Rank Test. This study found that movie is effective to improve student’s problem-solving skill. Based on the finding of the study, the counselors and future studies are suggested to consider effective media to help students to improve their problem-solving skill.